The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5664/jcsm.6990
|View full text |Cite
|
Sign up to set email alerts
|

Nightmares in United States Military Personnel With Sleep Disturbances

Abstract: Study Objectives: Sleep disturbances are common in United States military personnel. Despite their exposure to combat and trauma, little is known about nightmares in this population. The purpose of this study was to describe the prevalence and associated clinical and polysomnographic characteristics of nightmares in United States military personnel with sleep disturbances. Methods: Retrospective review of 500 active duty United States military personnel who underwent a sleep medicine evaluation and polysomnogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…More than two thirds of our treatment-seeking sample of CAF members and veterans reported being at least moderately bothered by sleep disturbances; and almost 90% reported being at least moderately bothered by trauma-related nightmares. Congruent with previous research, these findings emphasize that sleep difficulties are a common concern for military personnel and veterans [ 42 , 43 ], and echo the recent findings of Creamer and colleagues [ 44 ], who found that trauma-related nightmares were common amongst a cohort of 500 active duty United States military personnel. Our results also revealed that although sleep disturbances and nightmares were significantly associated with SI on their own, these associations seem to be mediated by depressive symptom severity, which is consistent with previous research supporting an indirect role of sleep disturbance [ 4 , 23 ].…”
Section: Discussionsupporting
confidence: 87%
“…More than two thirds of our treatment-seeking sample of CAF members and veterans reported being at least moderately bothered by sleep disturbances; and almost 90% reported being at least moderately bothered by trauma-related nightmares. Congruent with previous research, these findings emphasize that sleep difficulties are a common concern for military personnel and veterans [ 42 , 43 ], and echo the recent findings of Creamer and colleagues [ 44 ], who found that trauma-related nightmares were common amongst a cohort of 500 active duty United States military personnel. Our results also revealed that although sleep disturbances and nightmares were significantly associated with SI on their own, these associations seem to be mediated by depressive symptom severity, which is consistent with previous research supporting an indirect role of sleep disturbance [ 4 , 23 ].…”
Section: Discussionsupporting
confidence: 87%
“…Rates of nightmares seems to depend upon criteria, assessment, and methodology [16]. In a retrospective review of 500 active military personnel, Creamer et al [17•] found 31.2% had nightmares weekly, but only 3.9% reported nightmares as a reason for seeking treatment.…”
Section: Prevalence Of Sleep Disorder With Ptsdmentioning
confidence: 99%
“…
In his letter to the editor, Gupta alluded that the prolonged rapid eye movement (REM) sleep latency seen in our nightmare disorder (NDO) cohort could be an early marker for underlying psychiatric comorbidities, such as posttraumatic stress disorder (PTSD). 1,2 We concur that REM sleep abnormalities in patients with nightmares and trauma related nightmares are likely significant. REM fragmentation has been described following traumatic events, with increased REM density seen in patients with PTSD.
…”
mentioning
confidence: 58%